Interaction between intestinal microbiota and tumour immunity in the tumour microenvironment. Issue 3 (26th September 2021) - Yang, Xiuxiu; Guo, Yaxin; Chen, Chen; Shao, Bo; Zhao, Luyang; Zhou, Quanbo; Liu, Jinbo; Wang, Guixian; Yuan, Weitang; Sun, Zhenqiang
Abstract: In recent years, an increasing number of studies have reported that intestinal microbiota have an important effect on tumour immunity by affecting the tumour microenvironment (TME). The intestinal microbiota are closely associated with various immune cells, such as T lymphocytes, natural killer cells (NK cells) and macrophages. Some bacteria, such as Akkermansia muciniphila (A . muciniphila) and Lactobacillus reuteri (L . reuteri), have been shown to improve the effect of tumour immunity. Furthermore, microbial imbalance, such as the increased abundance of Fusobacterium nucleatum (F . nucleatum) and Helicobacter hepaticus (H . hepaticus), generally causes tumour formation and progression. In addition, some microbiota also play important roles in tumour immunotherapy, especially PD‐L1‐related therapies. Therefore, what is the relationship between these processes and how do they affect each other? In this review, we summarize the interactions and corresponding mechanisms among the intestinal microbiota, immune system and TME to facilitate the research and development of new targeted drugs and provide new approaches to tumour therapy. Abstract : We systematically explored the relationship among intestinal microbiota, immunity and tumour microenvironment. Besides, we also discussed the combined effect of gut microbiota and ICB. In short, the potential of gut microbiota in tumour therapy is promising.